2021
DOI: 10.9740/mhc.2021.05.211
|View full text |Cite
|
Sign up to set email alerts
|

The use of the ketogenic diet in the treatment of psychiatric disorders

Abstract: Introduction The ketogenic diet (KD) is a high-fat, low-carbohydrate, and moderate-protein diet that has shown benefit as a treatment in neurologic disorders and may serve as a therapeutic option in individuals with psychiatric disorders. Methods A search was conducted using EBSCOhost and PubMed databases for studies relating to ketogenic or low-carbohydrate diets and psychiatric disorders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The MIND diet significantly slows cognitive decline with age ( 92 ). The Mediterranean diet has also been shown to have a protective effect on anxiety and mental stress ( 93 ).…”
Section: Review Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The MIND diet significantly slows cognitive decline with age ( 92 ). The Mediterranean diet has also been shown to have a protective effect on anxiety and mental stress ( 93 ).…”
Section: Review Methodologymentioning
confidence: 99%
“…Other reported benefits included positive biometric changes such as improvements in lipid profile, weight reduction, positive change in blood glucose, and reduction in HbA1c. These benefits may facilitate the management of comorbidities and improve overall health and well-being ( 93 ). This highlights that advances in nutritional psychiatry are important and it will be important to replicate, refine and scale up dietary intervention studies targeting the prevention and treatment of common mental health disorders.…”
Section: Review Methodologymentioning
confidence: 99%
“…The KD also demonstrated an improvement in auditory hallucinations, mood, energy, the ability to concentrate, and sociability in patients with schizoaffective disorder (Kraeuter et al., 2019). A literature review concerning the use of the KD in treating other psychiatric disorders demonstrated that the KD displays merit as a potential complementary treatment option for anorexia nervosa, ASD, bipolar disorder, and narcolepsy, in addition to schizophrenia (Tillery et al., 2021). The KD has also shown to be effective in treating treatment refractory mental illness, resulting in significant improvements in depression and psychosis symptoms (Danan et al., 2022).…”
Section: Therapeutic Potential Of Manipulating Glucose and Ketone Met...mentioning
confidence: 99%
“…KD is also the subject of numerous studies in the treatment of psychiatric diseases, such as anorexia nervosa, autism spectrum disorders, bipolar disorder, narcolepsy and schizophrenia. In all of these, KD can reduce the severity of clinical symptoms [84].…”
Section: Effect Of Kd On Cancer Cells and Gene Expressionmentioning
confidence: 99%